EFEKTIVITAS VIDEO ANIMASI DALAM PENURUNAN NILAI INDEKS PLAK - Raket Rizki Rahmaningtyas; Widodo Widodo; Galuh Dwinta Sari; Diana Wibowo; Didit Aspriyanto (Dentin, 2025)
Background: Dental plaque, as a microbial biofilm, is the main causative factor for caries. The 2018 Riskesdas survey showed that the proportion of dental and oral problems reached 57.6%, with damaged, cavitated, or painful teeth accounting for 45.3%. Only 2.8% of the population practiced correct tooth-brushing behavior, resulting in poor oral hygiene and plaque accumulation. Educational methods using animated videos are needed to improve tooth-brushing techniques in a more effective and easily understandable manner. Purpose: To analyze the effectiveness of animated videos in reducing plaque index values among students aged 7–9 years at SDN Marabahan 2. Methods: This study employed a quasi-experimental method with a pretest-posttest group design. The population consisted of students at SDN Marabahan 2, and 50 respondents were selected through simple random sampling. Results: The paired t-test revealed a significant decrease in plaque index values following the animated video education intervention, with a p-value of <0,001 (p<0,05). Conclusion: Animated videos are an effective and efficient health education medium for oral health promotion programs, demonstrating significant reduction in plaque index values. Keywords:  Dental health education, animated videos, plaque index